Adherence to the Street Code Predicts an Earlier Anticipated Death. (March 2020) - Wolff, Kevin T.; Intravia, Jonathan; Baglivio, Michael T.; Piquero, Alex R.
Objectives: Criminologists have long been interested in the relationship between subcultural attitudes and antisocial behavior, with Anderson's street code thesis being the most recent and often researched foray in this area. Relatedly, scholars have begun to investigate the risk factors associated with the anticipation of early death. Extant research, however, has yet to empirically test Anderson's hypothesis that subscription to the street code is predictive of an anticipated early death. This study contributes to the literatures on the street code as well as fatalism by investigating the link between these two constructs. Methods: Using data from a sample of serious youthful offenders, we examine whether street code values are related to the anticipation of a short life span using a number of multivariate regression techniques controlling for a range of individual- and community-level variables. Results: Results show adherence to the street code is significantly associated with an anticipated early death among the sample of delinquent youth. Further, the relationship between street code and anticipated early death holds across race/ethnicity and gender, and results are not sensitive to the measurement of an anticipated early death. Findings from the current research are discussed, along with implications for policy and future research.